1962
DOI: 10.1002/j.1551-8833.1962.tb00967.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Quantitative Estimation of Synthetic Organic Pesticides by Chromatography

Abstract: This article begins by presenting a brief overview of the development and use of synthetic organic pesticides. Paper and gas chromatographic detection methods are discussed for analyses of pesticide residues in water, with the use of gas chromatography showing more promise. Results of gas chromatographic analysis, using argon and electron capture ionization detectors, of gamma BHC show that sensitivity of detection is increased with decrease in voltage in the detector cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1963
1963
1975
1975

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Three new reviews on paper chromatography are available (547,966,1446)• It was used for qualitative analysis of herbicides (484) and chlorinated (338,441,881,1060,1062,1558,1625) and phosphorus-containing (444,546,800,852,1137) pesticides.…”
Section: Antibioticsmentioning
confidence: 99%
“…Three new reviews on paper chromatography are available (547,966,1446)• It was used for qualitative analysis of herbicides (484) and chlorinated (338,441,881,1060,1062,1558,1625) and phosphorus-containing (444,546,800,852,1137) pesticides.…”
Section: Antibioticsmentioning
confidence: 99%
“…Numerous studies 11 have shown that repeated application of pesticides, particularly the chlorinated-hydrocarbon types, have resulted in substantial accumulation of pesticide residue in soil layers, ranging up to hundreds of pounds per acre.…”
Section: Pesticidesmentioning
confidence: 99%